Neutralizing activity to SARS‐CoV‐2 of convalescent and control plasma used in a randomized controlled trial. Issue 5 (19th February 2021) - Freedenberg, Alex T.; Pan, Chun‐Hao; Diehl, William E.; Romeiser, Jamie L.; Hwang, Ga‐Ram; Leiton, Cindy V.; Muecksch, Frauke; Shroyer, Kenneth R.; Bennett‐Guerrero, Elliott
Abstract: Background: There are limited data on the neutralizing activity of convalescent plasma (CP) administered in randomized controlled trials (RCT) of COVID‐19 infection. Study Design and Methods: As part of an RCT, CP was collected per FDA guidelines from individuals recovered from COVID‐19 infection. CP donors had to have ≥145 optical density (OD) units (ideal target ≥300) using a semiquantitative, immunochromatographic test for IgG antibody to the nucleocapsid protein (NP) of SARS‐CoV‐2 (typical range 0–500 OD units). A random subset of samples [14 control plasma, 12 CP "medium‐anti‐NP" (145–299 OD units), and 13 CP "high" anti‐NP (≥300 OD units)] were tested for neutralizing antibodies using an established viral luciferase antibody inhibition assay to detect the infection of SARS‐CoV‐2 pseudovirus that encoded spike protein (SARS2‐Strunc ) on a human immunodeficiency virus 1 vector (NL43dEnvNanoLuc), using ACE2‐expressing 293 T cells. The titer needed to neutralize 50% of viral activity (NT50) was calculated. Results: The uptake of SARS‐CoV‐2 pseudovirus by 293TACE2 cells was inhibited by pretreatment with CP compared to control CP ( p  < .001) with control plasma having a median (IQR) 50% neutralization titer (NT50) of 1:28 (1:16, 1:36) compared to 1:334 (1:130, 1:1295) and 1:324 (1:244, 1:578), for medium anti‐NP and high anti‐NP CP units, respectively. The neutralizing activity of CP met minimum FDA criteria with neutralizing antibody titers >1:80 in 100% of randomly selected samples, using a conservative approach that excluded non‐specific binding. Discussion: Plasma from donors screened using an immunochromatographic test for IgG antibody to SARS‐CoV‐2 NP exhibited neutralizing activity meeting FDA's minimum standard in all randomly selected COVID‐19 CP units.